Una aproximación histórica a la violencia de género. Precisiones conceptuales y cuantitativas sobre la sevicia conyugal en Lima durante las postrimerías coloniales (1795-1820) - Bustamante Otero, Luis (2018)
The study of private life has been a task usually retracted by Peruvian historiography, if not limited to anecdotal, curious or exotic aspects. In this sense, topics such as that of family and its historical development await further research that will allow us to construct a more integral vision of our past. From the analysis of judicial sources, the present work intends to enter into a scarcely explored terrain, that of conjugal violence, showing that the later colonial times formed a conjuncture marked by an increase of the domestic violence, also an expression of the colonial crisis. Specifically, it is intended to demonstrate that the set of judicial cases involving domestic violence in Lima between 1795 and 1820 exceeded the calculations and estimates with great length, placing the Peruvian capital in a controversial position of leadership in Latin America: 358 contentious proceedings in which the conjugal mistreatment was present, supported by multiple cases related to conjugal conflicts kept at the Lima Archbishopic Archives and at the National Archives. The analysis of the sources will also allow us to corroborate the undoubted role of women in the conjugal dramas that involved domestic violence, as well as the presence of battered men (albeit to a lesser extent) and the existence of marriages where the violence of both parties seemed to be the norm and the way of life, observing, likewise, that the conjugal mistreatment was present in all the social sectors, although the major incidences are related to the intermediate and popular segments. The scrutiny of judicial cases will also make it possible to account for the profession or office of the litigants, when expressly stated, as well as the indiscriminate use of the terms “don” and “doña” and the existence of interracial marriages, some of which associated violence with racism and xenophobia.